2019
DOI: 10.1111/jsr.12853
|View full text |Cite
|
Sign up to set email alerts
|

The effects of zolpidem in obstructive sleep apnea – An open‐label pilot study

Abstract: New knowledge on hypnotics and their effects on the phenotypic causes of obstructive sleep apnea indicate that zolpidem has therapeutic potential for certain patients. Specifically, zolpidem increases the threshold for arousal threshold and pharyngeal dilator muscle responsiveness. However, the effects of a standard dose of zolpidem (10 mg) on obstructive sleep apnea severity and symptoms have not been investigated. In an open‐label pilot study, 12 unselected people with obstructive sleep apnea were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The lack of a sytematic effect of zolpidem on AHI is consistent with our pilot study findings (Carberry et al 2019) and earlier preliminary reports (Cirignotta et al 1988;George et al 2010). It is also consistent with recent acute single dose, 1 month of nightly use and acute high dose findings with zopiclone (Carter et al 2016(Carter et al , 2018(Carter et al , 2020.…”
Section: Effects Of Zolpidem On Osa Severity and Sleep Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…The lack of a sytematic effect of zolpidem on AHI is consistent with our pilot study findings (Carberry et al 2019) and earlier preliminary reports (Cirignotta et al 1988;George et al 2010). It is also consistent with recent acute single dose, 1 month of nightly use and acute high dose findings with zopiclone (Carter et al 2016(Carter et al , 2018(Carter et al , 2020.…”
Section: Effects Of Zolpidem On Osa Severity and Sleep Parameterssupporting
confidence: 92%
“…This indicates that zolpidem improves two key contributors to OSA (arousal threshold and muscle responsiveness), and may therefore, have superior therapeutic potential to reduce OSA severity compared to other common hypnotics. Our recent open-label pilot study in 12 unselected OSA patients indicated that zolpidem was safe and well-tolerated (Carberry et al 2019).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, compared to placebo, they found no difference in AHI or oxygen saturation. Zolpidem 10 mg was again recently tested by Carberry et al [121] in an open label pilot study including 12 OSA patients administered the drug for a single night after a diagnostic polysomnography. There was no systematic effect on oxygen saturation or AHI (which changed minimally from 29 to 33 events/h), but sleep efficiency significantly improved from 77 to 84% on the drug night.…”
Section: Arousal Thresholdmentioning
confidence: 99%
“…7,8 Pharmacotherapeutic interventions should be low-risk to minimize burdening emergency departments saturated with patients who have COVID-19 and serve to reduce symptoms that interfere with behavioral activation. While the research on benzodiazepines and non-benzodiazepine receptor agonists ("Z-drugs" such as zolpidem and eszopiclone) in the setting of obstructive sleep apnea is complex, and there is some evidence that the latter may not exacerbate apnea, 9 benzodiazepines and Z-drugs are associated with an array of risks, including tolerance, withdrawal, and traumatic falls, particularly in older adults. 10 Sleep hygiene and cognitive-behavioral therapy are firstline therapies for insomnia.…”
Section: Clinical Pointmentioning
confidence: 99%